How Do Firms Cope with Economic Shocks in Real Time? - Thiemo Fetzer; Christina Palmou; Jakob Schneebacher (CESifo GmbH, 2024)
We study how businesses adjust to significant rises in energy costs. This matters for both the current energy crisis and the longer-term shift towards Net Zero. Using firm-level real-time survey and administrative data backed by a pre-registered analysis plan, we examine how firms respond to the energy price shock triggered by Russia's invasion of Ukraine along output, price, input, process and survival margins. We find that, on average, firms pass on some cost increases, build up cash reserves, and face higher debt, but do not yet see layoffs or bankruptcies. However, effects are highly heterogeneous by size and industry: for instance, small firms tend to increase cash reserves and prices, while large firms invest more in capital. We estimate separate elasticities for many small industry cells and subsequently use k-means clustering techniques on the estimated effects to identify high-dimensional firm-adaptation archetypes. These estimates can help tailor firm support in the energy transition both in the short and the long term. More generally, the machinery developed in this paper enables policymakers to evaluate and adjust economic policy in near-real time.
Keywords: D22; D24; H23; L11; O30; 330; energy price shock; firm dynamics; climate change; high-dimensional analysis